Too much of a good thing: Immune reconstitution inflammatory syndrome in a patient with Still's disease. (October 2022) - Batool, Nuzhat; Song, David; Almas, Talal; Alsubai, Abdulla K.; Thakur, Tushar; Ismail, Hebatalla; Alsufyani, Majid; Hadeed, Sebastian; Huang, Helen; Kotait, Farida; Aldhaheri, Khaled Saeed Obaid; Sindi, Atif Bakr; et al.
Abstract: Immune Reconstitution Inflammatory Syndrome (IRIS) is a potential complication when treating non HIV immunosuppressed patients with opportunistic infections. We present a case of a 49-year-old female with Adult-onset Still's disease on prednisone 40 mg daily who came to ED with right leg weakness and intractable headache for one week. She was diagnosed with Cryptococcus meningitis. Patient completed the induction phase of antifungal therapy and the steroids were tapered over four weeks. One month after discharge, a patient was brought in to ED, minimally responsive to verbal stimuli and had new left hemiparesis with persistent right leg weakness was noted on exam. An MRI of the brain was consistent with diffuse leptomeningeal enhancement compatible with meningoencephalitis. LP was notable for elevated opening pressure of 36cmH2O and CSF studies were negative for recurrence of cryptococcal infection. Given the timeline of patients presentation one month after discontinuation of steroids, and workup consistent with sterile meningitis, immune reconstitution inflammatory syndrome was identified as the likely diagnosis. The patient was started on 50 mg of Prednisone daily. Six weeks after presentation, the patient's mental status returned to baseline, left hemiparesis resolved, and right lower extremity strength significantly improved. Clinicians should have a high index of suspicion for CNS IRIS in patients presenting with new neurologic findings in the setting of rapid discontinuation of steroids due to infection. IRIS in HIV patients with cryptococcal meningitis is a well-established entity; the purpose of this case report is to bring attention to similar inflammatory syndrome in non-HIV patients with cryptococcal meningitis. Highlights: Immune Reconstitution Inflammatory Syndrome is a potential complication when treating non HIV immunosuppressed patients with opportunistic infections. Clinicians should have a high index of suspicion for CNS IRIS in patients presenting with new neurologic findings in the setting of rapid discontinuation of steroids due to infection. IRIS in HIV patients with cryptococcal meningitis is a well-established entity; the purpose of this case report is to bring attention to similar inflammatory syndrome in non HIV patients with cryptococcal meningitis.